Rock Mass, Geotechnical and Rock Type Identification Using SASW and MASW Methodsat Kajang Rock Quarry, Semenyih, Selangor Darul Ehsan - Kausarian, Husnul (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
Rockmass characterization study at Kajang Rock quarry wasperformed usingSpectral Analysisof Surface Waves (SASW) and Multichannel Analysis of Surface Waves (MASW) methods. RockQuality Designation (RQD) can be measured in the field directly. Discontinuity and processing survey methods determinedfrom 4 locations that have been examined in this study area. Based on MASW and SASW methods, velocity of S waves (Vs) can be obtained and weathering grade of rock mass has beenclassified. Location 1 consists of 5 weathering zones, SASW data indicates surface wave velocity (Vs) obtained from 198 m/s to 2044 m/s, MASW (Vs) ranges obtained from 2400 m/s. Location 2 consists of 4 weatheringzones, (Vs) of SASW obtained from 592 m/s to 2271 m/sand (Vs) of MASW obtained from 400 to 2000 m/s. Location 3 consists of 4 weathering zones with (Vs) of SASW obtained from 512 m/s to 2465 m/s and (Vs)of MASW obtained from 400 to >1200 m/s. Location 4 consists of 5 weathering grades with (Vs) of SASW obtained from the 200 m/s to 2040 m/s and (Vs) of MASW obtained from 300 to >2300 m/s. Rock Quality Designation (RQD) in Location 1 shown the rockquality is excellent (98.63%), in Location 2, RQD shows the rock is good (98.38%), in Location 3 RQD shows the rock is excellent (99.03%), in Location 4 RQD shows the rock is excellent (96.43%).